Kolaborasi Model Salafi Dan Khalafi Dalam Pendidikan Pesantren Dan Implikasinya Terhadap Upaya Peningkatan Mutu Santri - Nuzzulul Ulum (FKIP Universitas Islam Jember, 2018)
The main problem in this study is how the collaboration of the salafi and khalafi models in Islamic boarding schools education and their implications for efforts to improve the quality of students in PP. Darul Hikam Kertonegoro Jenggawah Jember? This study used a qualitative-descriptive approach. Data were collected from observation, interviews and documentation. Determination of informants using the snow-ball technique. The data that has been collected is analyzed using display, reduction and verification data analysis techniques, checking the validity of the data using triangulation techniques. From the analysis carried out, it can be concluded that the form of collaboration of the salafi and khalafi models is the salafi pattern combined with the khalafi pattern such as the centralistic pattern of pesantren in the kyai and then implemented by the badal kyai or administrators using good management. Keywords: Collaboration, salafi model, khalafi